2002
DOI: 10.1093/treephys/22.15-16.1125
|View full text |Cite
|
Sign up to set email alerts
|

Midday stomatal closure in Norway spruce--reactions in the upper and lower crown

Abstract: We used local microclimatic conditions and twig sap flow rates to interpret midday stomatal closure in the canopies of two 250-year-old Norway spruce (Picea abies (L.) Karst.) trees at a subalpine site in the Swiss Alps (1,650 m a.s.l.). Both trees showed midday stomatal closure on most clear summer days, despite the permanently wet soil. We used a modified Penman-Monteith formula to simulate potential transpiration of single twigs (ET(T)) based on high-resolution temporal and spatial microclimate data obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 60 publications
1
44
3
Order By: Relevance
“…5C-E). The increase in leaf temperature might be associated with the possible closure of stomata at midday [51]. Therefore, by down-regulating the PSII operating efficiency through increasing NPQ might cause an increase in photorespiration when CO2…”
Section: The Quantum Efficiency Of Psii (φPsii) Yield For Dissipatiomentioning
confidence: 99%
“…5C-E). The increase in leaf temperature might be associated with the possible closure of stomata at midday [51]. Therefore, by down-regulating the PSII operating efficiency through increasing NPQ might cause an increase in photorespiration when CO2…”
Section: The Quantum Efficiency Of Psii (φPsii) Yield For Dissipatiomentioning
confidence: 99%
“…The assumption is that this ratio is mainly dependent on soil water supply. However, [60] showed that Norway spruce reacts to high midday vapor pressure deficits (VPD) by closing stomata. Thus, the trees physiologically reduce their own transpiration activity on many days of the growing season.…”
Section: Parameterizing the Feddes Model Using Sap Flow Datamentioning
confidence: 99%
“…Nevertheless, since the Feddes approach is differentiated into h 3,high and h 3,low , atmospheric stress can be considered by adapting the T 0 range at which h 3 is a function of T 0 . The study of [60] suggests that spruce trees reduce transpiration when midday vapor pressure deficit exceeds 1250 Pa independent of soil wetness. Accordingly, we analyzed days with maximum VPD of approx.…”
Section: Parameterizing the Feddes Model Using Sap Flow Datamentioning
confidence: 99%
“…Terrestrial plants have mechanisms of internal water flux regulation, which uncouple plant water status from atmospheric, and soil hydrological control linked to morphological and physiological traits (ZWEIFEL et al, 2002).…”
Section: Final Considerationsmentioning
confidence: 99%